Key Account Management in Business-to-Business Markets An Assessment of Its Economic Value - Wengler, Stefan; SpringerLink (Online service) (Wiesbaden : Deutscher Universitätsverlag : Imprint: Deutscher Universitätsverlag, 2006)
In times of fierce competition in business-to-business markets strong and economically sound business relationships with a company's customers rank among the main success factors. As a well established marketing management conception, key account management is of particular significance in this context. Interestingly enough, empirical research studies have recently proved that relationship marketing, and particularly key account management, does not achieve the economic value originally expected. Stefan Wengler provides a well founded answer to the question of the economic value and shows the need for the implementation of key account management. He presents a comprehensive, but easy-to-handle decision-making model that supports the decision on the most efficient key account management organization for individual companies. In addition, the author gives a comprehensive overview on the key account management conception and its controlling tools.
State-of-the-art of key account management in academia and science -- Key account management controlling -- Analyzing key account management from the perspective of transaction cost economics -- Challenging the organization: the implementation of key account management -- Determining the economic value of key account management in business relationships -- Management implications -- Conclusion.
Keywords: Marketing; Marketing